Building a community lightsource meta-infrastructure to accelerate battery innovation in Europe - Sandrine Lyonnard; Caterina Biscari; Benedetto Bozzini; Montse Casas-Cabanas; Barbara Machado Calisto; Matilda Fransson; Rita Graceffa; Franz Hennies; Bernd Hinrichsen; Martin Karlsson; Elmar Kataev; Maya Kiskinova; et al. (JPhys Energy)
Breakthroughs in battery research are imperative to provide society with batteries that are safe and sustainable, have a high energy density, and have a long cycle life at low cost. Recent advances in research methodologies, the emergence of new market opportunities, and strategic funding schemes have allowed not only large, but also small companies, universities, and public research organizations to play an increasingly significant role in the advancement of battery technology. Challenges in battery technology development are multifaceted; therefore, a collaborative approach is crucial to bring together various stakeholders and ensure access to the full range of technical and scientific expertise. To grasp the core properties of electrode materials, electrolytes, and interfaces and to identify the mechanisms of battery degradation and failure, a multidisciplinary analytical approach is crucial. This strategy relies on the unique and complementary potential of advanced characterization techniques available at synchrotron and x-ray free electron laser facilities. Science-to-industry interactions are expected to increase the development of new standardized setups to approach realistic operando conditions. Therefore, rapid access to instruments, including high-throughput ex-situ , in-situ and operando capabilities, is key to accelerating the development of safe and sustainable batteries. The purpose of this paper is to discuss how the characterization needs of the battery community can be met by establishing a collaboration network based on a meta-infrastructure model, where the emphasis will be on collaboration and the sharing of experience and data. The proposed methodology considers the urgency in the battery community and the necessary technical developments to reach the scope of collaboration and focuses in particular on the needs for standardization, big data challenges, and open data approaches.